Peningkatan Kesadaran Cinta Tanah Air melalui Pendidikan Agama Katolik dan Budi Pekerti di SMP 5 Jagoi Babang - Simbolon Simbolon; Gregorius Daru Wijoyoko (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to analyze and describe the enhancement of students’ patriotic awareness through the implementation of the Catholic Religious Education and Character Formation (PAKBP) subject at SMP 5 Jagoi Babang. The research is grounded in the urgent need to cultivate nationalistic values from an early age, particularly in border areas, to safeguard students from external influences that may erode their sense of pride in being Indonesian citizens. A qualitative approach employing Classroom Action Research (CAR) was used and conducted in several cycles, consisting of planning, implementation, observation, and reflection stages. The participants were students of grades VII, VIII, and IX at SMP 5 Jagoi Babang. Data were collected through classroom observations of students’ participation, interviews with PAKBP teachers and students, and document analysis of lesson plans (RPP) integrating patriotic values. The indicators of success were identified through positive behavioral and attitudinal changes reflecting love for the homeland, such as active participation in flag ceremonies, respect for national symbols, and environmental stewardship within the school. The findings revealed a significant improvement in students’ patriotic awareness following the structured and contextually relevant application of PAKBP learning. Teachers successfully linked core Catholic faith teachings with the sociocultural and civic context, emphasizing the importance of being responsible citizens in accordance with Christian values. This implementation proved effective in fostering a spirit of nationalism that became internalized in the students’ daily attitudes and practices, both within the school and in the broader community.